Optimizing CSR Funds as a Source of Funding for Regional Development in Indonesia - Iskandar (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
The limited source of development funding forced the local government to find an innovative alternative. One of them is Corporate Social Responsibility (CSR). Although the prospect of CSR Funds as a source of local revenue is relatively big, mismanaging it could lead to a fraud which causes an underachieving the purpose of CSR itself. This paper specifically discussed an alternative budgeting process for local government’s activities that CSR was its source of fund. The purpose of this paper is to provide applicable suggestions for local government in optimizing CSR Funds as a source of local development funding that minimizing the potential fraud. To achieve this objective, this paper used a qualitative approach through analysis of relevant regulations and previous studies. This paper argued that receiving CSR Funds in the form of goods or services could help local government to reduce the risk of fraud, both from a local financial management perspective and from the CSR point of view. In addition to assisting local government with an alternative optimization source of development funding, this paper also contributed to providing input for the preparation of the National Medium-Term Development Plan (RPJMN) 2020-2024 that is intertwined with the Sustainable Development Goals (SDGs). The proposed strategies were divided into short-term, medium-term, and long-term policies such that it can be implemented with clear and measurable targets.